Evaluating the feasibility of Cas9 overexpression in 3T3-L1 cells for generation of genetic knock-out adipocyte cell lines. (1st January 2021) - Suchý, Tomás; Kaczmarek, Isabell; Maricic, Tomislav; Zieschang, Christian; Schöneberg, Torsten; Thor, Doreen; Liebscher, Ines
ABSTRACT: Cell lines recapitulating physiological processes can represent alternatives to animal or human studies. The 3T3-L1 cell line is used to mimic adipocyte function and differentiation. Since transfection of 3T3-L1 cells is difficult, we used a modified 3T3-L1 cell line overexpressing Cas9 for a straightforward generation of gene knock-outs. As an example, we intended to generate 3T3-L1 cell lines deficient for adhesion G protein-coupled receptors Gpr64/Adgr2 and Gpr126/Adgr6 using the CRISPR/Cas approach. Surprisingly, all the generated knock-out as well as scramble control cell lines were unresponsive to isoprenaline in respect to adiponectin secretion and lipolysis in contrast to the wild type 3T3-L1 cells. We, therefore, analysed the properties of these stable Cas9-overexpressing 3T3-L1 cells. We demonstrate that this commercially available cell line exhibits dysfunction in cAMP signalling pathways as well as reduced insulin sensitivity independent of gRNA transfection. We tried transient transfection of plasmids harbouring Cas9 as well as direct introduction of the Cas9 protein as alternate approaches to the stable expression of this enzyme. We find that transfection of the Cas9 protein is not only feasible but also does not impair adipogenesis and, therefore, represents a preferable alternative to achieve genetic knock-out.